(untitled) (Scientific journal of the Fergana State University, 2024)
This article talks about the works of D.S. Merezhkovsky, who founded neomythology in Russian literature at the beginning of the 20th century. The mythological synthesis manifested in his works in the genres of important artistic creativity, journalism and literary criticism is the basis for clarifying the types of thinking of the writer. D.S. Merezhkovsky’s religious-philosophical views, mythopoetic artistic creations, journalistic works dedicated to mature Russian writers, which have attracted the attention of many literary experts and philosophers, require serious attention to the work of the writer recognized as the "father of Russian symbolism".